Development of a Web-Based Cash Receipt Accounting Information System at the BNN Pratama Clinic, Banjarmasin City - Fitria; Emy Iryanie; Heldalina (International Journal of Integrated Science and Technology, 2024)
The BNN City Health Clinic in Banjarmasin requires an effective and efficient system to manage cash receipt records to ensure smooth operations and optimal health services. In this research, the author employs a qualitative method using both qualitative and quantitative data, with data collection methods including interviews, observations, and literature studies. The author highlights the issue of manual cash receipt recording, which not only reduces effectiveness and efficiency but also increases the likelihood of errors. The author recommends the immediate design and implementation of an accounting information system specifically designed for the purpose of recording cash receipts. This system must be able to accurately record every transaction, issue payment receipts, and generate the necessary financial reports. Additionally, we must implement the segregation of duties in the cash receipt process to mitigate the risk of errors and fraud. It is also important to implement strict internal controls to ensure transaction accuracy and auditability.